A systematic review of the efficacy of repetitive transcranial magnetic stimulation in treating dysarthria in patients with Parkinson's disease - Kerong Chen; Sitong Zhou; Shiyu Lu; Yuliang Qin; Xinyao Li; Yi Li; Tianyun Liu; Mei Zhang; Kun Xu; Hongping Shi; Xiaoman Lv; Kai Yuan; et al. (Frontiers in Aging Neuroscience)
ObjectiveTo analyze the literature on the efficacy of repetitive transcranial magnetic stimulation (rTMS) in treating dysarthria in patients with Parkinson's disease (PD) and provide a reference for targeted clinical treatment of dysarthria in PD patients.MethodsA systematic search was conducted in English and Chinese databases, including Embase, Cochrane, Medline, PubMed, CNKI, Wanfang, Chinese Biomedical Literature Database, and VIP Database, for relevant literature on rTMS treatment for dysarthria in PD patients. The search timeframe was from the inception of each database to October 2023. Literature was screened according to inclusion and exclusion criteria. Two researchers extracted information on study subjects, age, intervention methods, intervention duration, intervention frequency, evaluation indicators, and intervention results from the included literature. The modified Jadad scale was used to evaluate the quality of the literature.ResultsA total of seven studies were included, mainly focusing on the frequency, duration, and stimulation site of rTMS for dysarthria in PD patients. Six studies indicated that rTMS treatment improved dysarthria in PD patients.ConclusionRepetitive transcranial magnetic stimulation has a positive effect on improving dysarthria in PD patients, but further research is needed to determine its efficacy.